2016
DOI: 10.5812/ijem.33273
|View full text |Cite
|
Sign up to set email alerts
|

Altered Concentrations of Copper, Zinc, and Iron are Associated With Increased Levels of Glycated Hemoglobin in Patients With Type 2 Diabetes Mellitus and Their First-Degree Relatives

Abstract: BackgroundThe altered levels of some essential trace elements and antioxidant minerals have been observed in diabetic patients.ObjectivesThe aim of the present study was to compare the concentrations of essential trace elements, copper (Cu), zinc (Zn), and iron (Fe) in the serum of patients who have type 2 diabetes mellitus (T2DM) with those of their non-diabetic first-degree relatives (FDR) and control subjects. The association between glycated hemoglobin (HbA1c) and levels of metals was also evaluated.Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 58 publications
(64 reference statements)
2
27
1
1
Order By: Relevance
“…Secondly, excess iron deposition culminates in hyperinsulinemia due to obstruction in the insulin withdrawing ability of the liver [ 27 ]. Such deposits hinder insulin action, resulting in insulin resistance, which suppresses the yield of glucose in the liver [ 28 ].A similar trend has been observed in previous studies [ 29 , 30 , 31 , 32 , 33 ]. Poor glycaemic control is the root cause of escalated protein glycation—especially haemoglobin, which restores the free state of iron.…”
Section: Discussionsupporting
confidence: 92%
“…Secondly, excess iron deposition culminates in hyperinsulinemia due to obstruction in the insulin withdrawing ability of the liver [ 27 ]. Such deposits hinder insulin action, resulting in insulin resistance, which suppresses the yield of glucose in the liver [ 28 ].A similar trend has been observed in previous studies [ 29 , 30 , 31 , 32 , 33 ]. Poor glycaemic control is the root cause of escalated protein glycation—especially haemoglobin, which restores the free state of iron.…”
Section: Discussionsupporting
confidence: 92%
“…2d) but not in males or females only. Previous studies have found that plasma copper concentration do not correlate with HbA1c concentration in T1DM but positively correlates in T2DM (Ruiz et al 1998;Atari-Hajipirloo et al 2016). Plasma magnesium concentration negatively correlated with HbA1c concentration in T1DM when looking at both sexes Fig.…”
Section: Relationship Between Plasma Metal Concentrations and Hba1c Cmentioning
confidence: 67%
“…2m respectively) but not in males or females only. In previous publications, the zinc/copper ratio was also negatively correlated in T1DM and T2DM (Lin et al 2014;Atari-Hajipirloo et al 2016). Correlation of HbA1c concentration with total plasma metal concentrations could potentially be explained by glycation or oxidationassociated modifications of metal ion transport proteins (Abdelmagid et al 2015), formation of glycocholate (anion of the bile acid glycholic acid) that can complex and excrete metals in bile (Atari-Hajipirloo et al 2016) or abnormal insulin signalling leading to dysregulated metal homeostasis (McNair et al 1982;Gommers et al 2016).…”
Section: Relationship Between Plasma Metal Concentrations and Hba1c Cmentioning
confidence: 84%
See 1 more Smart Citation
“…An imbalance in the metabolism of Cu has been linked to hypercholesterolemia and an increased Cu:Zn superoxide dismutase was detected in obese individuals [89]. This obvious opposition between Zn and Cu has been acknowledged in hypertension [90], type 2 diabetes [91] and elevated blood pressure [92]. Zn can have an endogenous protective role against dyslipidemia and arteriosclerosis as it can inhibit the oxidation of LDL-C and protect against inflammatory diseases by inhibiting the activation of oxidative stress [82,93].…”
Section: Discussionmentioning
confidence: 99%